Serological detection of human parvovirus B19 infection and associated risk factors among pregnant women in Jigawa State, Nigeria. Issue 4 (4th July 2021) - Safiyanu, Mansur Bala; Akande, Azeez Oyebanji; Babayo, Adamu; Umar, Jamila; Abdullahi, Idris Nasir
ABSTRACT: Human Parvovirus B19 (B19 V) infection is hyperendemic in Nigeria. Pregnant women are not classically immunocompromised but maybe physiologically immunosuppressed and susceptible to viral infection. However, there is a paucity of studies on the epidemiology of B19V in Jigawa State, Northwestern Nigeria. This study aims to determine the seroprevalence, sociodemographic, and risk factors of human B19V infection among present women attending antenatal clinics of Jahun General Hospital, Nigeria. Between 2 February and 30 June 2019, blood samples were collected from 200 consented pregnant women and analyzed for anti-B19V IgM and IgG using commercially available enzyme-linked immunosorbent assay (ELISA). Sociodemographic and risk factors of subjects were collated through pre-tested structured questionnaires. Data generated were statistically analyzed for the association of anti-B19V and subjects' variables studied. Overall, the seroprevalence of anti-B19V IgM and IgG among pregnant women attending antenatal clinics of Jahun General Hospital, Nigeria was 6.0% and 22.5%, respectively. There was no significant association between the seroprevalence of anti-B19V IgM and anti-B19V IgG with all the sociodemographic variables and risk factors of pregnant women ( P  ˃0.05). However, pregnant women with a history of blood transfusion had a significant risk associated with seroprevalence of B19V IgM (OR = 5.95; 95% CI: 1.96–22.76;  P  = .009). Findings from this study revealed that a high proportion of the pregnant women were susceptible to B19V infection and anti-B19V IgG immunity decreased with age. Given the incidence of acute B19V infection, it is clinically important to continuously monitor their erythrocytes indices and screen their neonates for B19V infection and fetal complications.